Perlindungan Konsumen Terhadap Peredaran Makanan Kadaluwarsa di Kota Surakarta (Implementasi Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen) - Chasanah, Immawati Uswatun; Buana, Nimas (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The purpose of this study is to find out consumer protection against the circulation of expired food in the city of Surakarta reviewed from Law Number 8 of 1999 concerning Consumer Protection and to find out the efforts made by the government in tackling the circulation of expired food. The approach method uses empirical juridical. . The result obtained that legal protection for consumers related to the circulation of expired food is reviewed from Law Number 8 of 1999, consumers have the right to comfort, security, and safety in consuming food must meet quality standards. Consumer protection from the circulation of expired food is carried out coaching and supervision starting from supervision from business actors, production facilities and infrastructure, the overall business climate by related agencies such as BPOM, Disperindag, BPSK, Satpol PP Surakarta City, in accordance with Article 29 and Article 30 of Law Number 8 of 1999. The form of legal protection for consumers against the circulation and trade of expired food is preventive legal protection and repressive legal protection. If consumers do not get responsibility from the business actors for the losses suffered, then consumers can report it to the Surakarta City Consumer Dispute Resolution Agency. Consumer dispute resolution can be done by litigation and non-litigation. Efforts made by the government to overcome the circulation of expired meals, namely from agencies in general give warnings in writing and orally, and administrative sanctions in the form of compensation. The form of legal protection for consumers against the circulation and trade of expired food is preventive legal protection and repressive legal protection. If consumers do not get responsibility from the business actors for the losses suffered, then consumers can report it to the Surakarta City Consumer Dispute Resolution Agency. Consumer dispute resolution can be done by litigation and non-litigation. Efforts made by the government to overcome the circulation of expired meals, namely from agencies in general give warnings in writing and orally, and administrative sanctions in the form of compensation. Keywords: Expired Food, Consumer Protection Abstrak Tujuan dari penelitian ini adalah untuk mengetahui perlindungan konsumen terhadap peredaran makanan kadarluwarsa di Kota Surakarta ditinjau dari Undang-Undang Nomor 8 tahun 1999 tentang Perlindungan Konsumen dan untuk mengetahui upaya yang dilakukan pemerintah dalam menanggulangi peredaran makanan kadaluwarsa. Metode pendekatan menggunakan yuridis empiris. Hasil yang didapat bahwa Perlindungan hukum terhadap konsumen terkait peredaran makanan kadarluwarsa ditinjau dari Undang-Undang Nomor 8 tahun 1999, konsumen memiliki hak atas kenyamanan, keamanan, dan keselamatan dalam mengkonsumsi makanan harus memenuhi standar mutu. Perlindungan konsumen dari peredaran makanan kadaluwarsa maka dilakukan pembinaan dan pengawasan mulai dari pengawasan dari pelaku usaha, sarana dan prasarana produksi, iklim usaha secara keseluruhan oleh Instansi terkait seperti BPOM, Disperindag, BPSK, Satpol PP Kota Surakarta, sesuai Pasal 29 dan Pasal 30 Undang-Undang Nomor 8 Tahun 1999. Bentuk perlindungan hukum terhadap konsumen terhadap peredaran dan perdagangan makanan kadaluarsa adalah perlindungan hukum secara preventif dan perlindungan hukum secara represif. Jika konsumen tidak mendapatkan pertanggungjawab dari pihak pelaku usaha terhadap kerugian yang diderita, maka konsumen dapat melaporkannya kepada Badan Penyelesaian Sengketa Konsumen Kota Surakarta. Penyelesaian sengketa konsumen dapat dilakukan dengan cara litigasi dan non litigasi. Upaya yang dilakukan pemerintah untuk menanggulangi peredaran makan kadaluwarsa, yaitu dari pihak instansi secara umum memberi peringatan secara tertulis maupun lisan, dan sanksi administratif berupa ganti rugi. Kata Kunci: Makanan Kadaluwarsa, Perlindungan Konsumen